Prevalence Of Musculoskeletal Disorders In Patients Undergoing Haemodialysis in a Tertiary Care Hospital: A Cross-sectional study - Jayaprakash, Sanjaitha; Anap, Deepak B. (International Journal of Clinical and Biomedical Research, 2020)
Background: Chronic kidney disease (CKD) is a significant public health problem. Dialysis is the mainstream method of treatment in these patients. This causes the patients to have a monotonous and restricted daily life, joint pain, limiting their activities after treatment onset. Hence this study was carried out to find the prevalence of common musculoskeletal disorders in patients undergoing haemodialysis in a tertiary care hospital. Method: 50 participants undergoing dialysis in a tertiary care hospital under the age group of 18-70 years diagnosed with stage V CKD were included using convenient sampling. They were assessed using Nordic Questionnaire to locate the different areas of pain. Result: The first group consisted of 41 participants who underwent dialysis from 2- 41 months. Body regions commonly affected in the last 7 days were low back 25(60.97%); neck 21(51.21%); shoulder 15(36.58%); elbow 14(34.14%) in the extremity with arteriovenous fistula; upper back 14(34.14%); hips/thighs, knees 9(21.95); wrist/hands 7(17.07%) in the extremity with arteriovenous fistula; ankle/feet 6(14.63%). The second group consisted of 9 participants who underwent dialysis from 42-84 months. Body regions commonly affected in the last 7 days were low back 8(88.88%); upper back 7(77.77%); hip/thigh 6(66.66%); neck, knee 5(55.55%); elbow 4(44.44%) in the extremity with arteriovenous fistula; shoulder, ankle/feet, wrist/hands 3(33.33%). Conclusion: The study concluded that the highest prevalence of musculoskeletal disorders in the participants undergoing haemodialysis was low back pain (66%) followed by neck (52%), upper back (42%), shoulder (36%), elbow (36%), hips/thighs (30%), knees (28%), wrist/hands (20%) and ankle/feet pain (18%).